PRICE EARNING RATIO, DIVIDEN YIELD, DAN MARKET TO BOOK RATIO UNTUK MEMPREDIKSI RETURN ON STOCK MARKET - Sely Megawati Wahyudi (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2017)
The existence of the capital market makes the company has tools to measure the performance and financial condition of the company. If the company's financial condition is good, then the market will respond positively through an increase in stock prices. With the rise in stock prices in the capital market, more and more investors will invest in investments. In general, investors will invest if the investment can get the maximum return with certain risks. The stock valuation in fundamental analysis is often used by market analysis to determine the capital investment for the share Price Earning Ratio (PER), Market to Ratia Book, and Dividend Yield. In this research, the data used is secondary data. Samples are taken by systematic samples. This study uses regression analysis, Stock Return as the dependent variable and PER, MTB, DY and NI as independent variables. The results of the research conducted in the regression analysis were 32.6% in 2010, 25.5% in 2011, 26.3% in 2012 and 20.8% in 2010-2012. PER variables, MTB, DY, and NI for Returning Shares. This means that PER, MTB, DY, and NI simultaneously affect Stock Return. MTB positive effect on Stock Return, while PER, DY and NI negative effect on Stock Return, and four independent variables, MTB variable is the most dominant variable effect on Stock Return